Implementasi Pengenalan Hukum Islam di Madrasah dalam Membangun Keadilan, Kemaslahatan, dan Karakter Peserta Didik - Sofyan Suri (Bunayya: Jurnal Pendidikan Guru Madrasah Ibtidaiyah, 2025)
This study aims to examine the implementation of the introduction of Islamic law in madrasas in building the values ??of justice, welfare, and character of students. The background of this study is based on the importance of internalizing Islamic legal values ??not only as normative knowledge, but also as behavioral guidelines that shape students' personalities in everyday life. This study uses a qualitative approach with a library research type. Data sources were obtained from various scientific literature such as books, journal articles, and Islamic education policy documents relevant to the focus of the study. Data analysis was conducted using content analysis techniques and descriptive interpretation to obtain a comprehensive understanding of the application of Islamic law in madrasas. The results show that the introduction of Islamic law in madrasas is implemented through integration in Islamic Religious Education subjects, specifically fiqh, aqidah akhlak, and the Qur'an and Hadith, and is reinforced through religious culture and teacher role models. This implementation not only emphasizes cognitive aspects, but also affective and psychomotor aspects through the habituation of worship and the formation of Islamic character. Furthermore, the introduction of Islamic law has been proven to play a role in instilling values ??of justice, such as honesty and responsibility, and realizing the common good through the creation of a harmonious and humanistic educational environment. Furthermore, this process significantly contributes to the development of religious, disciplined, and noble character in students. Therefore, the implementation of Islamic law in madrasas plays a strategic role in shaping a generation that not only understands Islamic law theoretically but is also able to apply it in real life, as a manifestation of the holistic goals of Islamic education, oriented towards the welfare of the community.